Alcohol Is Longitudinally Associated with Lower Urinary Tract Symptoms Partially Via High‐Density Lipoprotein. (14th November 2014) - Suh, Beomseok; Shin, Dong Wook; Hwang, Seung‐sik; Choi, Ho‐Chun; Kwon, Hyuktae; Cho, BeLong; Park, Jin Ho
<x xml:space="preserve">Abstract</x> Background Previous studies on the association of alcohol consumption with lower urinary tract symptoms (LUTS) have been inconsistent, and none took into account the dynamic nature of LUTS, fluctuating over time. The purpose of the study was to determine the longitudinal association of alcohol consumption with LUTS. Methods We used generalized estimating equations to analyze the longitudinal association of alcohol consumption with LUTS in a longitudinal study of 9, 712 healthy men 30 years or older who visited our institution multiple times for routine comprehensive health evaluations, with an average follow‐up period of 27.9 months. Results Light–moderate alcohol consumption (0.1 to 29 g/d) was associated with decreased likelihood of moderate–severe LUTS, whereas heavy alcohol consumption (≥30 g/d) was associated with increased likelihood of moderate–severe LUTS in a dose‐dependent manner. Compared to those with 0 g/d alcohol intake, subjects who drank 0.1 to 9.9, 10 to 19.9, 20 to 29.9, 30 to 39.9, or ≥40 g/d of alcohol were in general significantly associated with moderate–severe LUTS with adjusted odds ratio (95% confidence interval) as follows respectively: 0.94 (0.87 to 1.02), 1.00 (0.91 to 1.09), 0.85 (0.77 to 0.93), 1.08 (0.98 to 1.19), and 1.31 (1.19 to 1.44). However, the protective association of light–moderate alcohol consumption with LUTS was greatly attenuated when serum high‐density lipoprotein (HDL) was added to the analysis, specifically for voiding symptoms. Conclusions We show strong evidence there is longitudinal association of alcohol consumption with LUTS. The protective effect of light–moderate alcohol consumption on LUTS is in part modulated by HDL as a confounder, similar to its effect on coronary heart disease.